2009
DOI: 10.1002/art.24759
|View full text |Cite
|
Sign up to set email alerts
|

TRAF1 polymorphisms associated with rheumatoid arthritis susceptibility in Asians and in Caucasians

Abstract: Objective. Recent genome-wide association scans and replication studies of European populations have disclosed several single-nucleotide polymorphisms (SNPs) associated with rheumatoid arthritis (RA) susceptibility. The aim of this study was to evaluate the RA-associated loci by genotyping previously reported SNPs and additional tag SNPs in a Korean population.Methods. A total of 1,316 unrelated RA patients and 1,006 controls were genotyped for 12 SNPs identified in genome-wide scans and for 12 additional tag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 32 publications
4
41
0
Order By: Relevance
“…Electronic and manual searches resulted in the identification of 30 studies, and 11 were selected for full-text review based on their titles and abstracts [9][10][11][12][13][14][15][16][17][18]27]. One study was excluded because it contained no extractable data [27].…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic and manual searches resulted in the identification of 30 studies, and 11 were selected for full-text review based on their titles and abstracts [9][10][11][12][13][14][15][16][17][18]27]. One study was excluded because it contained no extractable data [27].…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…One study was excluded because it contained no extractable data [27]. Thus, ten studies were considered in this meta-analysis [9][10][11][12][13][14][15][16][17][18], and comprised six European, two Asian, one African-American, and one Tunisian population (Table 1). Meta-analyses were conducted separately on the rs6920220, rs10499194, and rs2230926 polymorphisms.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Even within a similar ethnic group, the association of some candidate genetic markers to RA was differently reported. For example, polymorphisms in OLIG3 or TNFAIP3 genes were reported to be significantly associated with RA in Japanese (Kochi et al, 2010) but not in Korean population (Han et al, 2009). Recent meta-analysis of GWAS also suggested that only a small amount of the genetic component can be explained by the known RA risk alleles (Raychaudhuri et al, 2008;Stahl et al, 2010).…”
Section: Figure 1 Gwas Results and Plots In The Region Around Apom (A)mentioning
confidence: 99%
“…[87][88][89][90][91][92] Specifically, a study of 3962 RA patients and 3531 healthy controls demonstrated strong association (OR = 1.2; 95% CI: 1.1-1.3; P = 2.6 × 10 -6 ) with a variant (rs6920220) in an intergenic region of chromosome 6q23 region between oligodendrocyte linear transcription factor 3 (OLIG3) and TNF-α-induced protein 3 (TNFAIP3). 91 The validity of this study has been confirmed by a recent metaanalysis of seven studies investigating the association of the TNFAIP3-OLIG3 region with RA, which indicated a strong association of the variant rs6920220 (OR = 1.2, 95% CI: 1.2-1.3; P = 7.9 × 10 -17 ).…”
Section: Tnfaip3-olig3 Is Associated With Ra Pathogenesismentioning
confidence: 99%